IBM FlashSystem and VMware Implementation and Best Practices Guide - Bolland, Duane; Fincher, Jordan; Green, David; Gucer, Vasfi; Hawkins, Warren; Ibrahim, Rufai; Torolho, Leandro (IBM Redbooks, 2021)
This IBM® Redbooks® publication details the configuration and best practices for using IBM's FlashSystem family of storage products within a VMware environment. This book was published in 2021 and specifically addresses Spectrum Virtualize Version 8.4 with VMware vSphere Version 7.0. Topics illustrate planning, configuring, operations, and preferred practices that include integration of FlashSystem storage systems with the VMware vCloud suite of applications: - vSphere Web Client (VWC) - vStorage APIs for Storage Awareness (VASA) - vStorage APIs for Array Integration (VAAI) - Site Recovery Manager (SRM) - vSphere Metro Storage Cluster (vMSC) This book is intended for presales consulting engineers, sales engineers, and IBM clients who want to deploy IBM FlashSystem® storage systems in virtualized data centers that are based on VMware vSphere.
Online resource; Title from title page (viewed July 19, 2021)